Appropriate Concentration of Glycerin Solution for the Preservation of Fresh Cadaveric Vessels to be Used in Surgical Training: A Preliminary Study - Kitkhuandee, Nawiya; Kitkhuandee, Natcha; Utsaha, Sorawich (Thai Journal of Neurological Surgery, 2025)
Background: Training neurosurgeons on cadaveric blood vessels poses challenges in maintaining lifelike tissue properties for realistic surgical practice. This study aimed to determine the optimal glycerin concentration for preserving fresh cadaveric arteries while retaining flexibility, consistency, color, and fragility resembling living vessels. Methods: Arterial vessels from two human placentas were harvested, trimmed to ≥5 cm lengths, and divided into five groups of three arteries each. The groups were embalmed in glycerin solutions of 3%, 10%, 20%, 40%, and 60% concentrations, respectively. After two years frozen at -20˚C and two days at 5˚C for slow thawing, the preserved arteries were evaluated by seven neurosurgeons. They performed cutting, suturing, and repair procedures, then rated satisfaction levels across tissue elasticity, handling, consistency, smell, color, fragility, realism, and overall quality. Results: The arteries embalmed in 40% glycerin solution received the highest overall satisfaction ratings from surgeons. Conclusions: A 40% glycerin solution proved most appropriate for preserving placental arteries to achieve lifelike characteristics for neurosurgical training purposes. Further studies using human cadaveric arteries and varying storage durations are warranted.